Análise química da madeira tratada com CCA-C, do carvão vegetal e do licor pirolenhoso - Euflosino, Allan Ewerton Rezende (2015)
Wood treated, after the end of their service life is ruled out, most often, incorrectly, as waste is toxic. Measures to reuse or recycle this material are research being targeted in several countries. The research objectives were to evaluate the amount of chromated copper arsenate - CCA - C on waste wood treated and the effectiveness of the methodology used in order to reuse the decontaminated wood. The treated wood waste were processed into chips with dimensions of 0.50 x 3.0 x 3.0 cm (tangential x radial x longitudinal), and a part there of was ground in a Wiley mill and other carbonized. Charcoal, by-products of the carbonization and wood in the form of sawdust were assessed to determine the amount of CCA present in them. The sawdust and crushed coal solutions were extracted with 0.1 mol L-1 and the sulfuric acid and the sodium and potassium hydroxides acids, for two, four and six hours. The material of the extractions was washed and the amount of CCA - C present was assessed. The results showed that the most efficient extraction solution to remove the CCA wood and coal was sulfuric acid. The six-hour extraction time was what better results. It was also observed that the process of extraction of the product condom is more efficient when using wood, coal and which, during carbonization of wood treated portion of the oxides is released into the atmosphere, since the pyroligneous liquid obtained CCA in its composition. The results, both for wood as for coal were not enough for that waste is considered non-hazardous. The wood and coals after extracted and waste from the process of extraction of wood and coal, for the most part were considered dangerous, demanding greater attention to your disposal.